Tinjauan Hukum Terhadap Tanggung Jawab Sosial Perusahaan (Corporate Social Responsibility) - Rahmadany; Isdiana Syafitri; Atika Sandra Dewi; Daud (LEGAL BRIEF, 2022)
In many countries with developed industries, corporate social responsibility (CSR) is not a legal obligation, but an action that has ethical and moral dimensions so that its implementation is voluntary. In Indonesia, corporate responsibility is made a legal obligation that must be obeyed by the company as contained in Article 74 paragraph (1) of Law Number 40 of 2007 concerning Limited Liability Companies. In carrying out its activities, a Limited Liability Company must interact with various components related to it. In general, there are two components involved in the activities of a Limited Liability Company, the two components we know as shareholders and stakeholders. A shareholder is a component related to the internal of the Limited Liability Company, which in this case is known as the shareholders while what is meant by Stakeholders are all parties outside the shareholders who are related to the activities of the Limited Liability Company. The existence of a Limited Liability Company in a community environment must be able to make a positive contribution to the community concerned. There are many values ??and orders that have lived in a society that must be maintained with the emergence of a new element in their environment